SUPERVISION OF HOTEL AND RESTAURANT TAX LEARNING TO IMPROVE REGIONAL ORIGINAL INCOME (PAD) SUMEDANG DISTRICT - Lalas Sulastri; Prima Nugraha (JEES: Journal of Economic Empowerment Strategy, 2019)
To manage hotel and restaurant taxes, it is absolutely necessary to have sufficient supervision andto supervise the implementation of hotel and restaurant taxes carried out by the Regional RevenueService. The purpose of this study, namely to determine the implementation of supervision of hoteland restaurant tax collection, things that hinder and efforts that must be done to overcome obstaclesto the implementation of supervision of hotel and restaurant tax collection in increasing the originalrevenue of Sumedang Regency. The method used in this research is qualitative method. With eightinformants of research, namely the Head of the Regional Revenue Service, Head of Planning andOperations Control, Head of Control and Supervision Section, Executive Staff of OperationalControl Planning, hotel and restaurant management. The results of the study show that controllingof hotel tax collection and restaurant tax to increase Sumedang Regency's original revenue has beeneffective but not yet maximally this can be seen from still encountered several obstacles, includingthe competency of tax collector officers, budget constraints and low awareness of taxpayers.However, it is expected that in the future there will be improvements in line with efforts to be carriedout by the Regional Revenue Service of Sumedang Regency.